IDO and TDO inhibitors in cancer immunotherapy: mechanisms, clinical development, and future directions - Al-Zoubi, Raed M.; Elaarag, Mai; Al-Qudimat, Ahmad R.; Al-Hurani, Enas A.; Fares, Zainab E.; Farhan, Ala’a; Al-Zoubi, Sally R.; Khan, Abbas; Agouni, Abdelali; Shkoor, Mohanad; Bawadi, Hiba; Zakaria, Zain Z.; et al. (Frontiers in Pharmacology, 2025)
Indoleamine-2,3-dioxygenase (IDO) and tryptophan-2,3-dioxygenase (TDO) inhibitors are promising avenues in cancer immunotherapy. These enzymes are key regulators in the kynurenine pathway. modulating immune responses and enabling tumor immune evasion. By targeting IDO and TDO. Therapeutic approaches aim to restore immune surveillance and enhance antitumor activity. This review examines the mechanisms of IDO/TDO in cancer etiology, their consequences in the tumor microenvironment, and the therapeutic development of inhibitors currently being studied. Among these, medications like Indoximod, Epacadostat, and Navoximod have shown promise in influencing the immune system and slowing tumor progression, while dual inhibitors like HTI-1090 try to address broader metabolic connections. Despite tremendous progress, obstacles like tumor heterogeneity, off-target consequences, and varying patient responses remain. The use of IDO/TDO inhibitors with conventional anticancer medications demonstrates their potential to reshape cancer treatment paradigms, contingent on further research to optimize efficacy and safety.Clinical Trial Registration:https://clinicaltrials.gov/study/NCT03844438.